Foamed silicon carbide ceramics and their preparation and application

By using acid-etched pore-forming agents in silicon carbide ceramics to combine with alumina nanosheets to form a uniform pore structure, and by grafting modified carbon fibers with nano-aerogels and polyacrylic acid to improve adhesion, the problem of silicon carbide ceramics is solved The problems of uneven pore distribution, reduced strength and surface inertia achieve high mechanical strength and corrosion resistance.

CN118908744BActive Publication Date: 2025-01-21ZHONGKE ZHUOYI GREENE TECH (DONGGUAN) CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411169820.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-25
Publication Date
2025-01-21
Estimated Expiration
2044-08-25

AI Technical Summary

Technical Problem

The pore distribution of silicon carbide ceramics is uneven, the strength is reduced, and the surface inertness leads to poor additive binding force.

Method used

Acid-etched pore-forming agent is mixed with an organic binder and deposited on the surface of alumina nanosheets. It serves as a carrier for the pore-forming agent and provides a large number of binding sites to combine modified alumina nanosheets, cross-linking agents and silicon precursors. The porous structure nano-aerogel formed by the body is filled into the pores between silicon carbide particles, and the adhesion is improved by grafting polyacrylic acid to modify the carbon fiber.

Benefits of technology

The uniform pore structure of silicon carbide ceramics is achieved, the mechanical strength and corrosion resistance are improved, and the problems of uneven pore distribution and strength reduction are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005008946350000141
    Figure BDA0005008946350000141
Patent Text Reader

Abstract

The invention discloses foamed silicon carbide ceramics and its preparation and application, belonging to the technical field of porous ceramics, and the preparation method comprises the following steps: adding pretreated silicon carbide particles to a polyacrylic acid grafted carbon fiber dispersion, stirring, adding an inorganic binder, a nano-aerogel loaded with a pore-forming agent, and a sintering aid to mix, filtering, drying, and obtaining raw powder; placing the raw powder in a pulverizer for crushing, sieving, placing in a mold, performing molding, drying, and then placing in a high-temperature sintering furnace, heating, sintering, cooling to room temperature, and obtaining foamed silicon carbide ceramics. The nano-aerogel can be filled into the pores between silicon carbide particles. During the high-temperature sintering process, the pore-forming agent forms a molten fluid at high temperature, flows out through the pores of the aerogel, decomposes to form carbon dioxide gas, and passes through the uniform pores of the nano-aerogel, thereby giving the silicon carbide ceramics a uniform pore structure, thereby avoiding the uneven pore distribution of the silicon carbide ceramics caused by the loose pore-forming agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of porous ceramics, in particular to foamed silicon carbide ceramics and preparation and application thereof. Background Art

[0002] Foam ceramics have been widely used in aerospace, energy, chemical industry, environmental protection, biology and other fields due to their high specific surface area, low relative density, high wear resistance and thermal shock resistance. Among them, silicon carbide foam ceramics have been paid attention to and developed and applied by researchers in many fields, especially in high-temperature thermal protection systems and high-temperature gas filtration, due to their excellent high-temperature resistance, corrosion resistance and oxidation resistance.

[0003] Silicon carbide ceramics are mostly made using the pore-forming agent method, in which a pore-forming agent that is easily decomposed into gas when heated is added to the silicon carbide ceramic slurry, leaving holes in the silicon carbide ceramic structure to produce foam ceramics. However, the location of the pores is determined by the location of the pore-forming agent adhered to the silicon carbide particles, resulting in uneven pore distribution in the silicon carbide ceramics. In addition, silicon carbide produces brittle cristobalite during the sintering process, causing the strength of the porous ceramics to decrease. In addition, due to the strong covalent bonds in its molecular structure, silicon carbide has an inert surface and poor bonding with additives. Summary of the invention

[0004] The invention aims to provide foamed silicon carbide ceramics and preparation and application thereof: an acid-etched pore-forming agent is mixed with an organic binder and then deposited on the surface of an alumina nanosheet. The alumina nanosheet is used as a carrier of the pore-forming agent and can provide a large number of pore-forming agent binding sites, so that the pore-forming agent can be fixed on the surface of the alumina nanosheet to avoid uneven pore distribution caused by the loose binding of the pore-forming agent with silicon carbide particles; modified alumina nanosheets, a cross-linking agent and a silicon precursor are mixed, freeze-dried and then heat-treated to form a porous nano-aerogel that can be filled into the pores between silicon carbide particles; the pore-forming agent forms a molten fluid at a high temperature, flows out through the pores of the aerogel, decomposes to form carbon dioxide gas, passes through the uniform pores of the nano-aerogel, and then gives the silicon carbide ceramic a uniform pore structure; polyacrylic acid is grafted onto modified carbon fibers and then added to a resin solution; the carbon fibers have high fluidity and are filled into the pores; the mutually staggered arrangement structure can absorb stress and avoid the porous structure of the nano-aerogel being easily broken during the molding process.

[0005] Technical problems to be solved by the present invention: Silicon carbide ceramics are mostly made by a pore-forming agent method, in which a pore-forming agent that is easily decomposed into gas when heated is added to the silicon carbide ceramic slurry, leaving holes in the silicon carbide ceramic structure to produce foam ceramics, but the position of the pores is determined by the position of the pore-forming agent adhered to the silicon carbide particles, resulting in uneven pore distribution of the silicon carbide ceramics; and silicon carbide produces brittle cristobalite during the sintering process, resulting in a decrease in the strength of the porous ceramics; in addition, due to the strong covalent bond characteristics of its molecular structure, silicon carbide has an inert surface and poor bonding with additives.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The method for preparing foamed silicon carbide ceramics comprises the following steps:

[0008] S1. Add the pretreated silicon carbide particles to the polyacrylic acid grafted carbon fiber dispersion, stir, add an inorganic binder, a nano-aerogel loaded with a pore-forming agent, and a sintering aid to mix, filter, and dry to obtain raw powder.

[0009] Among them, the silicon hydroxyl and aluminum hydroxyl groups contained on the surface of the pretreated silicon carbide particles can be combined with the polyacrylic acid grafted carbon fibers through chemical bonds, so that the polyacrylic acid grafted carbon fibers are coated on the surface of the pretreated silicon carbide particles, giving them excellent adhesion, and adhering the inorganic binder, nano-aerogel loaded with pore-forming agent, and sintering aid to the surface of the silicon carbide particles, thereby increasing the contact area between the silicon carbide particles and the additives.

[0010] S2. The raw powder is crushed and sieved in a grinder, placed in a mold, molded, dried, and then placed in a high-temperature sintering furnace for heating and sintering, and cooled to room temperature to obtain foamed silicon carbide ceramics.

[0011] Furthermore, the inorganic binder is a mixture of potassium feldspar, kaolin, quartz and potassium carbonate in a mass ratio of 1.1-1.4:0.1-0.3:0.3-0.5:0.1-0.2.

[0012] Furthermore, the sintering aid is selected from any one of yttrium oxide, aluminum oxide and magnesium oxide.

[0013] Furthermore, the molding pressure is 150-250 MPa; and the mesh size is 200-300 meshes.

[0014] More preferably, the molding pressure is 230 MPa and the mesh size is 250 mesh.

[0015] Furthermore, the heating rate is 200-300°C / h, the sintering temperature is 1600-1800°C, and the sintering time is 2-4h.

[0016] Further preferably, the heating rate is 250° C. / h, the sintering temperature is 1700° C., and the sintering time is 3.5 h.

[0017] Furthermore, the pretreated silicon carbide particles are specifically prepared by the following steps: mixing the silicon carbide particles with aluminum sulfate, keeping the mixture at 900° C. for 1.5 hours, cooling to room temperature, washing, and drying to obtain the pretreated silicon carbide particles.

[0018] Among them, aluminum sulfate is mixed with silicon carbide particles. The sulfite generated by the high-temperature decomposition of aluminum sulfate at 900°C has extremely strong oxidizing properties, which can oxidize the SiC covalent bonds on the surface of silicon carbide particles, so that the SiC bonds on the surface of silicon carbide ceramics are converted into AlO bonds and SiO bonds, thereby improving its surface activity and making the silicon carbide particles have better dispersibility in the resin emulsion, avoiding the agglomeration of silicon carbide particles, resulting in a decrease in the mechanical properties of the formed silicon carbide ceramics and uneven pore distribution.

[0019] Furthermore, the mass ratio of silicon carbide particles to aluminum sulfate is 4-6:3-4.

[0020] Furthermore, the particle size of the silicon carbide particles is 10-75 μm.

[0021] Furthermore, the nano-aerogel loaded with the pore-forming agent is prepared by mixing the modified alumina nanosheets, the cross-linking agent and the silicon precursor, freeze-drying the mixture and then subjecting the mixture to heat treatment.

[0022] Furthermore, the silicon precursor is selected from tetraethyl orthosilicate, polydimethylsiloxane, polyphenylmethylsiloxane, and dimethyldiphenylpolysiloxane.

[0023] More preferably, the silicon precursor is selected from tetraethyl orthosilicate.

[0024] Furthermore, the cross-linking agent is selected from one of chitosan, polyethylene glycol and ethylene glycol.

[0025] Further preferably, the cross-linking agent is selected from chitosan.

[0026] Furthermore, the freeze-drying temperature is -(20-30)°C, and the freeze-drying time is 8-10h.

[0027] More preferably, the freeze-drying temperature is -25°C and the freeze-drying time is 9 hours.

[0028] Furthermore, the heat treatment temperature is 200-400° C., and the heat treatment time is 1-2 h.

[0029] More preferably, the heat treatment temperature is 300° C. and the heat treatment time is 1.5 h.

[0030] Furthermore, the nano-aerogel loaded with a pore-forming agent is prepared by the following steps:

[0031] The modified alumina nanosheets and a cross-linking agent with a mass fraction of 2% were stirred at a rate of 500 r / min for 2 hours, a silicon precursor and ethanol were added, and the mixture was stirred until gelation. The mixture was placed in a freezer and freeze-dried at -25°C for 9 hours to obtain an aerogel. The aerogel was heat-treated at 300°C for 1 hour and cooled to room temperature to obtain a nano aerogel loaded with a pore-forming agent.

[0032] Among them, the modified alumina nanosheets are mixed with the cross-linking agent chitosan solution to form a gel precursor with a high viscosity to maintain the dispersion stability of the modified alumina nanosheets. The hydrolyzate of the silicon precursor can undergo a cross-linking reaction with chitosan to form a gel structure of a cross-linked network. The surface of the modified alumina nanosheets contains oxygen-containing functional groups, which can also react with the gel precursor, so that the modified alumina nanosheets are embedded in the silica gel, thereby achieving the fixation of the modified alumina nanosheets by the silica gel. After drying, a porous nano aerogel structure is formed, and high-temperature treatment at 300°C is performed to decompose the cross-linking agent chitosan, thereby avoiding the influence of organic components on silicon carbide ceramics.

[0033] Furthermore, the usage ratio of modified alumina nanosheets, crosslinking agent, silicon precursor and ethanol is 0.7-0.8 g:15-25 mL:0.3-0.7 g:8-12 mL.

[0034] Furthermore, the modified alumina nanosheets are prepared by mixing an acid-etched pore-forming agent with an organic binder and then depositing the mixture onto the surface of the alumina nanosheets.

[0035] Furthermore, the organic binder is selected from any one of methyl cellulose, carboxymethyl cellulose and hydroxyethyl cellulose.

[0036] Furthermore, the diameter of the aluminum oxide nanosheets is 150-280 nm.

[0037] More preferably, the diameter of the aluminum oxide nanosheets is 200 nm.

[0038] Furthermore, the pore former is a mixture of graphite and activated carbon in a mass ratio of 1-2:1.2-1.4.

[0039] Further, the modified alumina nanosheets are prepared by the following steps:

[0040] The acid-etched pore-forming agent and organic binder were added to ethanol, stirred evenly, and alumina nanosheets were added. The reaction was stirred at 85°C for 30 minutes to allow the acid-etched pore-forming agent to adhere to the surface of the alumina nanosheets. The mixture was filtered, washed with deionized water for 3 times, and dried in an oven at 80°C for 10 minutes to obtain modified alumina nanosheets.

[0041] Among them, the graphite and activated carbon surfaces in the acid-etched pore former carry a large number of reactive functional groups, which can be combined with the oxygen-containing functional groups in the organic binder methyl cellulose through chemical bonds, giving the pore former adhesion properties, and then can be deposited on the surface of alumina nanosheets. The large number of aluminum hydroxyl groups contained on the surface of the alumina nanosheets can serve as carriers of the pore former and provide a large number of pore former binding sites, which can fix the pore former on the surface of the alumina nanosheets and avoid uneven pore distribution caused by the loose combination of the pore former and silicon carbide particles.

[0042] Furthermore, the usage ratio of the acid-etched pore-forming agent, the organic binder, ethanol, and the alumina nanosheets is 2.6-3 g: 0.3-0.7 g: 25-35 mL: 1.3-1.7 g.

[0043] Furthermore, the alumina nanosheets are specifically prepared by the following steps: adding aluminum nitrate nonahydrate and glucose to deionized water, stirring at 70°C until completely dissolved, placing in a 70°C vacuum drying oven for concentration for 30 minutes to obtain a viscous liquid, mixing the viscous liquid with 3.2g of ammonium chloride, heating to 1100°C, keeping warm for 1 hour, and cooling to room temperature to obtain alumina nanosheets.

[0044] Among them, glucose and aluminum nitrate nonahydrate are mixed to form a solution, which is concentrated by heating, and the glucose undergoes a thermal polymerization reaction, so that the solution forms a high-viscosity viscous liquid. The aluminum ions can be combined with the oxygen-containing functional groups in the glucose through chemical bonds and dispersed in the viscous liquid system. At a temperature of 1100°C, glucose and aluminum nitrate are thermally decomposed to form aluminum oxide nanosheets, which have high high temperature resistance and are not easy to melt and decompose at 1400°C.

[0045] Furthermore, the mass ratio of aluminum nitrate nonahydrate, glucose, deionized water, and ammonium chloride is 3.5-4:10.6-11:8-12.

[0046] Furthermore, the acid-etched pore-forming agent is prepared by the following steps: grinding the pore-forming agent into powder in a grinder, adding it to a 2.5 mol / L nitric acid aqueous solution, stirring at 60-80° C. for 25-35 min, filtering, washing, and drying to obtain the acid-etched pore-forming agent.

[0047] Furthermore, nitric acid can dissolve impurities on the surface of pore-forming agent graphite and activated carbon, and nitric acid has strong oxidizing activity, which can oxidize carbon atoms on the surface of pore-forming agent graphite and activated carbon into carboxyl groups and hydroxyl groups, so that the oxygen-containing functional groups on the surface of pore-forming agent graphite and activated carbon are exposed, have higher activity, and better adhere to the surface of silicon carbide particles.

[0048] Furthermore, the usage ratio of the pore former and the nitric acid solution is 2-2.2 g:15-25 mL.

[0049] Furthermore, the polyacrylic acid grafted carbon fiber dispersion is prepared by adding polyacrylic acid grafted modified carbon fiber into a resin solution.

[0050] Furthermore, the carbon fiber has a length of 0.5-2 μm and a diameter of 20-50 nm.

[0051] More preferably, the carbon fiber has a length of 1.5 μm and a diameter of 40 nm.

[0052] Furthermore, the resin solution is prepared by mixing bisphenol A epoxy resin, phenolic resin and ethanol in a dosage ratio of 2.5-2.7 g: 1-2 g: 100-120 mL.

[0053] Furthermore, the polyacrylic acid grafted carbon fiber dispersion is specifically prepared by the following steps:

[0054] Add carbon fiber to toluene, stir at 50°C for 0.5h, add benzoyl peroxide, heat to 95°C, continue stirring for 15min, add acrylic acid, ammonium persulfate and sodium methylene bisnaphthalene sulfonate, stir and react for 60min, filter, wash with deionized water 3 times, dry in an oven at 60°C for 10min to obtain polyacrylic acid grafted carbon fiber, add polyacrylic acid grafted carbon fiber to the resin solution, stir evenly to obtain polyacrylic acid grafted carbon fiber dispersion.

[0055] Among them, in the toluene solution, benzoyl peroxide is used as an activator for carbon fiber, so that the surface of carbon fiber carries active functional groups as polyacrylic acid polymerization sites. Under the action of the catalyst ammonium persulfate, acrylic acid is polymerized on the surface of carbon fiber to form polyacrylic acid grafted carbon fiber, which is mixed with the resin solution to form a dispersion. The polar functional groups contained in the dispersion can be combined with the oxygen-containing functional groups on the surface of the pretreated silicon carbide particles through chemical bonds, so that the carbon fiber adheres more firmly to the surface of the pretreated silicon carbide particles.

[0056] Furthermore, the mass ratio of carbon fiber, acrylic acid solution and ammonium persulfate is 1-1.2:2-2.2:0.04-0.06.

[0057] Furthermore, the present invention also provides the application of the silicon carbide ceramics prepared as above in the fields of high-temperature thermal protection materials and high-temperature gas filtration.

[0058] Furthermore, compared with the prior art, the present invention has the following beneficial effects:

[0059] (1) In the technical scheme of the present invention, the acid-etched pore-forming agent exposes the oxygen-containing functional groups on the surfaces of the pore-forming agent graphite and activated carbon, which have higher activity and better adhere to the surface of silicon carbide particles; the acid-etched pore-forming agent is deposited on the surface of alumina nanosheets. The large amount of aluminum hydroxyl groups contained on the surface of the alumina nanosheets, as a carrier of the pore-forming agent, can provide a large number of pore-forming agent binding sites, and can fix the pore-forming agent on the surface of the alumina nanosheets, thereby avoiding the uneven pore distribution caused by the weak binding of the pore-forming agent to the silicon carbide particles. In addition, the alumina nanosheets have higher high temperature resistance and are not easy to melt and decompose at 1400°C, so that the aerogel skeleton of the alumina nanosheet-based aerogel is not easy to decompose during the preparation of silicon carbide ceramics.

[0060] (2) In the technical scheme of the present invention, modified alumina nanosheets, a cross-linking agent and a silicon precursor are mixed to form a porous nano-aerogel that can be filled into the pores between silicon carbide particles. During the high-temperature sintering process, the pore-forming agent forms a molten fluid at high temperature, flows out through the pores of the aerogel, decomposes to form carbon dioxide gas, and passes through the uniform pores of the nano-aerogel, thereby giving the silicon carbide ceramic a uniform pore structure, thereby avoiding the pore-forming agent from adhering to the silicon carbide particles loosely, resulting in uneven pore distribution of the silicon carbide ceramic.

[0061] (3) In the technical solution of the present invention, the nano-aerogel can also be coated on the surface of silicon carbide particles. During the high-temperature sintering process, the alumina nanosheets in the nano-aerogel can react with the cristobalite produced by the silicon carbide particles during the sintering process to form mullite, thereby eliminating the brittle cristobalite produced by silicon carbide during the sintering process, and forming mullite with high mechanical strength on the surface of silicon carbide. The formed mullite tightly connects the nano-material with the silicon carbide particles, and the formed three-dimensional porous silicon carbide ceramic has high-temperature creep resistance and high mechanical strength. In addition, the nano-aerogel, as a silicon carbide ceramic filler, has excellent corrosion resistance and high temperature resistance.

[0062] (4) In the technical scheme of the present invention, the aluminum sulfate surface-coated silicon carbide particles are used to oxidize the SiC covalent bonds on the surface of the silicon carbide particles, so that the SiC bonds on the surface of the silicon carbide ceramics are converted into Al-O bonds and SiO bonds, thereby improving its surface activity, making the silicon carbide particles have better dispersibility in the resin emulsion, and avoiding the agglomeration of the silicon carbide particles, which leads to a decrease in the mechanical properties of the formed silicon carbide ceramics and uneven pore distribution; in the process of preparing silicon carbide ceramics, under high-temperature sintering, sulfur trioxide generated by the decomposition of aluminum sulfate reacts with silicon carbide to generate silicon oxide, and the formed silicon oxide can react with aluminum oxide in the nano-aerogel loaded with a pore-forming agent to generate mullite nanofibers and adhere to the surface of silicon carbide, which, on the one hand, improves the bonding force between the nano-aerogel and the silicon carbide ceramics, and on the other hand, the composite structure of the mullite fiber coating the surface of the silicon carbide forms a rough mullite surface layer, which increases the compactness between the silicon carbide particles, thereby enhancing the mechanical strength of the silicon carbide ceramics.

[0063] (5) In the technical scheme of the present invention, polyacrylic acid grafted carbon fiber is mixed with a resin solution as a dispersion liquid of silicon carbide particles, which can adhere to the surface of silicon carbide particles, impart excellent adhesion, and adhere fillers and additives to the surface of silicon carbide particles. During the sintering process, the carbon fiber has high fluidity and fills into the pores. Its staggered structure can absorb stress and avoid the easy breakage of the porous structure of the nano aerogel during the molding process. The carbon fiber also improves the compressive strength and corrosion resistance of the silicon carbide ceramic. DETAILED DESCRIPTION

[0064] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0065] The raw materials used in the examples of the present invention are as follows: aluminum sulfate (AR, purity 99.9%); chitosan (deacetylation degree 95.5%, viscosity 160 mPas, purchased from Shanghai McLean Biochemical Technology Co., Ltd.); tetraethyl orthosilicate (analytical grade, purchased from Sinopharm Chemical Reagent Co., Ltd.); carboxymethyl cellulose (model 9000-11-7, purchased from Shanghai Yuanye Biotechnology Co., Ltd.); aluminum nitrate nonahydrate (purity 99%; manufacturer: Shanghai McLean Biochemical Technology Co., Ltd.); glucose (analytical grade, manufacturer: Shanghai McLean Biochemical Technology Co., Ltd.); ammonium chloride (purity 99.6%); nitric acid aqueous solution (model 7697-37-2, concentration 2.5 mo l / L); benzoyl peroxide (model 94-36-0); acrylic acid (purity 99%, model 79-10-7); ammonium persulfate (purity 98.5%, model 7727-54-0); sodium methylene bisnaphthalene sulfonate (analytical grade AR, model 36290-04-7); bisphenol A type epoxy resin (E-44, solid content 80%, viscosity 8000-13000cps); phenolic resin (specification: industrial grade, manufacturer: Henan Huanshan Industrial Co., Ltd.); toluene (purity 99.8%, model 108-88-3).

[0066] Example 1

[0067] The nano-aerogel loaded with a pore-forming agent is prepared by the following steps:

[0068] A1. Add 3.75 g of aluminum nitrate nonahydrate and 10.8 g of glucose to 10 g of deionized water, stir at 70°C until completely dissolved, place in a 70°C vacuum drying oven for concentration for 30 min to obtain a viscous liquid, mix the viscous liquid with 3.2 g of ammonium chloride, heat to 1100°C, keep warm for 1 h, and cool to room temperature to obtain aluminum oxide nanosheets.

[0069] A2. Mix 1.5g of graphite and 1.3g of activated carbon as a pore-forming agent, grind 2.1g of the pore-forming agent in a grinder into powder, add it to 20mL of 2.5mol / L nitric acid aqueous solution, stir at 70°C for 30min, filter, wash with deionized water 3 times, and dry in an oven at 60°C for 10min to obtain an acid-etched pore-forming agent.

[0070] A3. Add 2.8g of acid-etched pore-forming agent and 0.5g of carboxymethyl cellulose to 30mL of ethanol, stir evenly, add 1.5g of alumina nanosheets, and react with stirring at 85°C for 30min to allow the acid-etched pore-forming agent to adhere to the surface of the alumina nanosheets. Filter, wash with deionized water 3 times, and dry in an oven at 80°C for 10min to obtain modified alumina nanosheets.

[0071] A4. Add 2 g of chitosan to 1 mL of acetic acid and 99 mL of deionized water, stir evenly to obtain chitosan with a mass fraction of 2%, stir 0.75 g of modified alumina nanosheets and 20 mL of chitosan with a mass fraction of 2% at 500 r / min for 2 h, add 0.5 g of tetraethyl orthosilicate and 10 mL of ethanol, stir until gelation, place in a freezer at -25°C, freeze-dry for 9 h to obtain aerogel, heat treat the aerogel at 300°C for 1 h, and cool to room temperature to obtain a nano aerogel loaded with a pore-forming agent.

[0072] Comparative Example 1

[0073] The difference between this comparative example and Example 1 is that the modified alumina nanosheets are replaced with an acid-etched pore-forming agent, and the remaining steps and raw materials are the same as those of Example 1.

[0074] Comparative Example 2

[0075] The difference between this comparative example and Example 1 is that the nano-aerogel loaded with the pore-forming agent is replaced by modified alumina nano-sheets, and the remaining steps and raw materials are the same as those of Example 1.

[0076] Example 2

[0077] The polyacrylic acid grafted carbon fiber dispersion is prepared by the following steps:

[0078] B1. Add 1.1 g of carbon fiber to 50 mL of toluene, stir at 50 ° C for 0.5 h, add 0.5 g of benzoyl peroxide, heat to 95 ° C, continue stirring for 15 min, add 2.1 g of acrylic acid, 0.05 g of ammonium persulfate and 0.04 g of sodium methylene bisnaphthalene sulfonate, stir and react for 60 min, filter, wash with deionized water 3 times, and dry in an oven at 60 ° C for 10 min to obtain polyacrylic acid grafted carbon fiber.

[0079] B2. Add 2.6 g of bisphenol A epoxy resin and 1.5 g of phenolic resin into 110 mL of ethanol, stir evenly to obtain a resin solution, add 2.5 g of polyacrylic acid grafted carbon fiber into the resin solution, stir evenly to obtain a polyacrylic acid grafted carbon fiber dispersion.

[0080] Comparative Example 3

[0081] The difference between this comparative example and Example 2 is that no carbon fiber is added.

[0082] Example 3

[0083] The preparation method of foamed silicon carbide ceramics comprises the following steps:

[0084] S1. 5 g of silicon carbide particles were mixed with 3.5 g of aluminum sulfate, kept at 900° C. for 1.5 h, cooled to room temperature, washed with deionized water three times, and dried in an oven at 70° C. for 10 min to obtain pretreated silicon carbide particles.

[0085] S2. 1.1 g of potassium feldspar, 0.1 g of kaolin, 0.3 g of quartz and 0.1 g of potassium carbonate are mixed to obtain an inorganic binder, 60 g of pretreated silicon carbide particles are added to 20 g of the polyacrylic acid grafted carbon fiber dispersion prepared in Example 2, and stirred, 1.5 g of inorganic binder, 2 g of the nano aerogel loaded with a pore-forming agent prepared in Example 1, and 0.7 g of yttrium oxide are added, and stirred evenly. The mixture is filtered, washed with deionized water 3 times, and dried in an oven at 70°C for 10 min to obtain raw powder.

[0086] S3. The raw powder prepared in step S2 is crushed in a grinder, passed through a 250-mesh sieve, placed in a mold, molded at a molding pressure of 230 MPa, dried at 80°C for 30 minutes, and then placed in a high-temperature sintering furnace, heated to 1700°C at a heating rate of 250°C / h, and sintered at 1700°C for 3.5 hours to obtain foamed silicon carbide ceramics.

[0087] Example 4

[0088] The method for preparing foamed silicon carbide ceramics comprises the following steps:

[0089] S1. 5 g of silicon carbide particles were mixed with 3.5 g of aluminum sulfate, kept at 900° C. for 1.5 h, cooled to room temperature, washed with deionized water three times, and dried in an oven at 70° C. for 10 min to obtain pretreated silicon carbide particles.

[0090] S2. 1.2 g of potassium feldspar, 0.2 g of kaolin, 0.4 g of quartz, and 0.15 g of potassium carbonate are mixed to obtain an inorganic binder, 70 g of pretreated silicon carbide particles are added to 30 g of the polyacrylic acid grafted carbon fiber dispersion prepared in Example 2, and stirred, 1.95 g of inorganic binder, 2.5 g of the nano aerogel loaded with a pore-forming agent prepared in Example 1, and 1.1 g of aluminum oxide are added, and stirred evenly. The mixture is filtered, washed with deionized water 3 times, and dried in an oven at 70°C for 10 min to obtain raw powder.

[0091] S3. The raw powder prepared in step S2 is crushed in a grinder, passed through a 250-mesh sieve, placed in a mold, molded at a molding pressure of 230 MPa, dried at 80°C for 30 minutes, and then placed in a high-temperature sintering furnace, heated to 1700°C at a heating rate of 250°C / h, sintered at 1700°C for 3.5 hours, and cooled to room temperature to obtain foamed silicon carbide ceramics.

[0092] Example 5

[0093] The method for preparing foamed silicon carbide ceramics comprises the following steps:

[0094] S1. 6 g of silicon carbide particles were mixed with 4 g of aluminum sulfate, kept at 900° C. for 1.5 h, cooled to room temperature, washed with deionized water three times, and dried in an oven at 70° C. for 10 min to obtain pretreated silicon carbide particles.

[0095] S2. 1.4 g of potassium feldspar, 0.3 g of kaolin, 0.5 g of quartz and 0.2 g of potassium carbonate are mixed to obtain an inorganic binder, 80 g of pretreated silicon carbide particles are added to 40 g of the polyacrylic acid grafted carbon fiber dispersion prepared in Example 2, and stirred, 2.4 g of inorganic binder, 3 g of the nano aerogel loaded with a pore-forming agent prepared in Example 1, and 1.5 g of magnesium oxide are added, and stirred evenly. The mixture is filtered, washed with deionized water 3 times, and dried in an oven at 70°C for 10 min to obtain raw powder.

[0096] S3. The raw powder prepared in step S2 is crushed in a grinder, passed through a 250-mesh sieve, placed in a mold, molded at a molding pressure of 230 MPa, dried at 80°C for 30 minutes, and then placed in a high-temperature sintering furnace, heated to 1700°C at a heating rate of 250°C / h, sintered at 1700°C for 3.5 hours, and cooled to room temperature to obtain foamed silicon carbide ceramics.

[0097] Comparative Example 4

[0098] The difference between this comparative example and Example 4 is that the nano-aerogel loaded with a pore-forming agent prepared in Example 1 is replaced by the material prepared in Comparative Example 1, and the remaining steps and raw materials are the same as those in Example 4.

[0099] Comparative Example 5

[0100] The difference between this comparative example and Example 4 is that the nano-aerogel loaded with pore-forming agent prepared in Example 1 is replaced by the material prepared in Comparative Example 2, and the remaining steps and raw materials are the same as those in Example 4.

[0101] Comparative Example 6

[0102] The difference between this comparative example and Example 4 is that the polyacrylic acid grafted carbon fiber dispersion prepared in Example 2 is replaced by the material prepared in Comparative Example 3, and the remaining steps and raw materials are the same as those in Example 4.

[0103] Comparative Example 7

[0104] The difference between this comparative example and Example 4 is that the pretreated silicon carbide particles are replaced with silicon carbide particles, and the remaining steps and raw materials are the same as Example 4.

[0105] The performance of the silicon carbide ceramics prepared in Examples 3-5 and Comparative Examples 4-7 is now tested.

[0106] The bending strength of the silicon carbide ceramics prepared above was tested according to GB / T1965-1996 standard; the porosity of the silicon carbide ceramics prepared above was tested according to GB / T1966-1996 standard; the pore size performance of the silicon carbide ceramics prepared above was tested according to GB / T1967-1996 standard; the thermal expansion coefficient of the silicon carbide ceramics prepared above was measured at 25-480°C using a German NETZSCH thermal dilatometer (DI L-402C model).

[0107] The corrosion resistance of porous silicon carbide ceramics was measured by measuring the weight loss rate of silicon carbide ceramics in acid and alkali solutions. The polished silicon carbide ceramics were placed in 20% hydrochloric acid and 20% sodium hydroxide solutions, respectively, for 1 hour, washed and dried, and then the weight loss was measured to detect the corrosion resistance of the silicon carbide ceramics prepared above. The test results are shown in Table 1 below.

[0108] Table 1 Test results

[0109]

[0110] It can be seen from the data in Table 1 that in Comparative Example 4, the modified alumina nanosheets are replaced with acid-etched pore-forming agents to prepare nano-aerogels loaded with pore-forming agents, which are used to prepare silicon carbide ceramics, and their porosity and mechanical properties decrease. This may be because the alumina nanosheets can provide a large number of pore-forming agent binding sites, which can fix the pore-forming agent on the surface of the alumina nanosheets, and avoid the pore-forming agent and silicon carbide particles from being loosely bound, resulting in uneven pore distribution; in Comparative Example 5, the nano-aerogels loaded with pore-forming agents are replaced with nano-aerogels loaded with pore-forming agents prepared by modified alumina nanosheets, and are used to prepare silicon carbide ceramics, and their porosity decreases and their pore distribution is uneven. This may be because during the high-temperature sintering process of the nano-aerogels, the pore-forming agent flows out through the pores of the aerogels to decompose and form carbon dioxide gas, which flows through the uniform pores of the nano-aerogels. gaps, thereby giving the silicon carbide ceramic a uniform pore structure; in Comparative Example 6, a polyacrylic acid grafted carbon fiber dispersion prepared without adding carbon fiber is used to prepare silicon carbide ceramics, and its corrosion resistance, mechanical properties and porosity are reduced. This may be because the carbon fiber has high fluidity and is filled into the pores. Its staggered arrangement structure can absorb stress and avoid the easy breakage of the porous structure of the nano aerogel during the molding process; Comparative Example 7 replaces the pretreated silicon carbide particles with silicon carbide particles to prepare silicon carbide ceramics, and its various properties are reduced compared with Example 4. This may be because the silicon carbide particles on the surface of aluminum sulfate increase their surface activity, so that the silicon carbide particles have better dispersibility in the resin solution, avoiding the agglomeration of silicon carbide particles, resulting in reduced mechanical properties and uneven pore distribution of the formed silicon carbide ceramics.

[0111] Compared with commercially available silicon carbide ceramics, the silicon carbide ceramics prepared by the present invention have higher porosity, continuous performance and thermal conductivity, and the pore size distribution is uniform.

[0112] The silicon carbide ceramics prepared by the present invention also include applications in the fields of high-temperature thermal protection materials and high-temperature gas filtration. In high-temperature thermal protection materials, the thermal expansion coefficient is 1.7×10 -6 / ℃, and the bending strength is 19.3MPa, indicating that the silicon carbide ceramics prepared by the present invention have higher thermal insulation performance and mechanical strength in high-temperature thermal protection materials; in the field of high-temperature gas filtration, it has high combustion rate, good stability, uniform heat evolution, no local high temperature, and low emissions of pollutants such as NOx and CO, thereby achieving stable combustion of low calorific value gases.

[0113] The data in Table 1 show that the silicon carbide ceramics prepared in Examples 3-5 not only have good high temperature resistance and high porosity, but also have uniform pore distribution of the silicon carbide ceramics. The pretreated silicon carbide particles are added to the polyacrylic acid grafted carbon fiber dispersion, stirred, and inorganic binders, nano-aerogels loaded with pore-forming agents, and sintering aids are added and mixed, filtered and dried to obtain raw powder, the raw powder is molded, placed in a pulverizer for crushing and sieving to obtain a green body, the green body is placed in a high-temperature sintering furnace for sintering, and cooled to room temperature. The prepared silicon carbide ceramics meet the test performance requirements, while the silicon carbide ceramics prepared in Comparative Examples 4-7 do not meet the performance requirements, indicating that the silicon carbide ceramics prepared by the present invention not only have good high temperature resistance and high porosity, but also have uniform pore distribution of the silicon carbide ceramics.

[0114] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0115] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing foamed silicon carbide ceramics, characterized in that: The following steps are involved: S1. The pretreated silicon carbide particles are added to the polyacrylic acid grafted carbon fiber dispersion, stirred, an inorganic binder, a nano-aerogel loaded with a pore-forming agent, and a sintering aid are added, mixed, filtered, and dried to obtain raw powder; The nano-aerogel loaded with a pore-forming agent is prepared by mixing modified alumina nanosheets, a cross-linking agent and a silicon precursor, freeze-drying the mixture, and then subjecting the mixture to a heat treatment. The modified alumina nanosheets are prepared by mixing an acid-etched pore-forming agent with an organic binder and then depositing the mixture on the surface of the alumina nanosheets. The polyacrylic acid grafted carbon fiber dispersion is prepared by grafting polyacrylic acid onto modified carbon fibers and then adding the modified carbon fibers into a resin solution. S2. The raw powder is crushed and sieved in a grinder, placed in a mold, molded, dried, and then placed in a high-temperature sintering furnace, heated, sintered, and cooled to room temperature to obtain a foamed silicon carbide ceramic; The silicon precursor is selected from tetraethyl orthosilicate, polydimethylsiloxane, polyphenylmethylsiloxane, dimethyldiphenylpolysiloxane; the crosslinking agent is chitosan; The freeze drying temperature is -(20-30)°C, and the freeze drying time is 2-4h; the heat treatment temperature is 200-400°C, and the heat treatment time is 1-2h; The acid-etched pore-forming agent is prepared by the following steps: grinding the pore-forming agent into powder in a grinder, adding the powder into a 2.5 mol / L nitric acid aqueous solution, stirring at 60-80° C. for 30 min, filtering, washing, and drying to obtain the acid-etched pore-forming agent; The ratio of the pore-forming agent to the nitric acid solution is 2-2.2 g: 15-25 mL; The pore-forming agent is formed by mixing graphite and activated carbon in a mass ratio of 1-2:1.2-1.4; The pretreated silicon carbide particles are specifically prepared by the following steps: mixing silicon carbide particles with aluminum sulfate, keeping the mixture at 900° C. for 1.5 hours, cooling the mixture to room temperature, washing the mixture, and drying the mixture to obtain pretreated silicon carbide particles; The mass ratio of the silicon carbide particles to aluminum sulfate is 4-6:3-4; the particle size of the silicon carbide particles is 10-75 μm.

2. The method for preparing foamed silicon carbide ceramics according to claim 1, characterized in that: The organic binder is selected from any one of methyl cellulose, carboxymethyl cellulose and hydroxyethyl cellulose; the diameter of the aluminum oxide nanosheet is 150-280nm; the length of the carbon fiber is 0.5-2μm and the diameter is 20-50nm.

3. The method for preparing foamed silicon carbide ceramics according to claim 1, characterized in that: The inorganic binder is formed by mixing potassium feldspar, kaolin, quartz and potassium carbonate in a mass ratio of (1.1-1.4):(0.1-0.3):(0.3-0.5):(0.1-0.2); the sintering aid is selected from any one of yttrium oxide, aluminum oxide and magnesium oxide.

4. The method for preparing foamed silicon carbide ceramics according to claim 1, characterized in that: The molding pressure is 150-250 MPa; the mesh size is 200-300 mesh; the heating rate is 200-300° C. / h, the sintering temperature is 1600-1800° C., and the sintering time is 2-4 hours.

5. Silicon carbide ceramics prepared according to the preparation method according to any one of claims 1 to 4.

6. Application of the silicon carbide ceramic according to claim 5 in the fields of high-temperature thermal protection materials and high-temperature gas filtration.

Citation Information

Patent Citations

  • High-strength silicon carbide ceramic and preparation method thereof

    CN108585905A

  • Micron-grade mesoporous graphene material

    CN109524647A